2006
DOI: 10.1371/journal.pone.0000070
|View full text |Cite
|
Sign up to set email alerts
|

Catalases Are NAD(P)H-Dependent Tellurite Reductases

Abstract: Reactive oxygen species damage intracellular targets and are implicated in cancer, genetic disease, mutagenesis, and aging. Catalases are among the key enzymatic defenses against one of the most physiologically abundant reactive oxygen species, hydrogen peroxide. The well-studied, heme-dependent catalases accelerate the rate of the dismutation of peroxide to molecular oxygen and water with near kinetic perfection. Many catalases also bind the cofactors NADPH and NADH tenaciously, but, surprisingly, NAD(P)H is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 53 publications
1
52
0
Order By: Relevance
“…Superoxide generation was evaluated using an in vitro tellurite reduction assay previously developed in our laboratory [34]. The system makes use of the O 2 − specific reactive compound WST-1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Superoxide generation was evaluated using an in vitro tellurite reduction assay previously developed in our laboratory [34]. The system makes use of the O 2 − specific reactive compound WST-1.…”
Section: Resultsmentioning
confidence: 99%
“…These results also favor the idea that tellurite does not produce peroxide inside E. coli as does the hydrogen peroxide-hypersensitive katG strain which showed a negligible increase in sensitivity to K 2 TeO 3 (Table 2). E. coli cells over expressing a Staphylococcus epidermidis catalase gene showed a slight increase in tellurite resistance suggesting that the role of H 2 O 2 in tellurite resistance, if any, is not an important feature of K 2 TeO 3 toxicity [34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found that YqhD was highly induced when cells were grown in the presence of K 2 TeO 3 . This result and the fact that an important pathway of tellurite toxicity involves superoxide generation (4,27) prompted us to evaluate the role that YqhD could have in E. coli resistance to tellurite and other oxidative stress elicitors.…”
Section: Discussionmentioning
confidence: 99%
“…Although cells overexpressing yqhD showed increased tolerance to compounds whose toxicity involves superoxide generation like paraquat and potassium tellurite (4,27), the hydroxyl radical-generating chromate anion (5), and hydrogen peroxide, E. coli ⌬yqhD showed increased sensitivity to all these compounds (Table 2). To assess whether YqhD-mediated resistance phenotype was also related to cytoplasm thiol depletion (especially GSH), the effect of YqhD on E. coli resistance to oxidant compounds that involve thiol oxidation like diamide and cadmium chloride (28) was determined.…”
Section: Yqhd Mediates Resistance To Ros Elicitors In E Coli-tomentioning
confidence: 99%